2012
DOI: 10.1037/a0025893
|View full text |Cite
|
Sign up to set email alerts
|

Eating when bored: Revision of the Emotional Eating Scale with a focus on boredom.

Abstract: These results suggest that boredom is an important construct, and that it should be considered a separate dimension of emotional eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 10 publications
5
86
0
5
Order By: Relevance
“…Moreover, leisure was associated with greater interest, which likely indicates lower boredom levels. As boredom and disengagement have been related to poor health behaviors, including drug and alcohol use, smoking, and greater eating [28][29][30][31][32][33], leisure activities may serve as protective factor on health behaviors. Extending beyond mood states, leisure was associated with lower reports of stress and lower objectively measured heart rate, suggesting that leisure may evoke a type of relaxation response [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, leisure was associated with greater interest, which likely indicates lower boredom levels. As boredom and disengagement have been related to poor health behaviors, including drug and alcohol use, smoking, and greater eating [28][29][30][31][32][33], leisure activities may serve as protective factor on health behaviors. Extending beyond mood states, leisure was associated with lower reports of stress and lower objectively measured heart rate, suggesting that leisure may evoke a type of relaxation response [52].…”
Section: Discussionmentioning
confidence: 99%
“…Interest also varies as a function of the activity one engages in and was assessed in the present study as a (negative) indicator of one's boredom levels. Prior work has linked greater levels of boredom with poor health behaviors, including greater drug use [28,29] and eating [30,31]. Moreover, those who report more boredom during leisure time also report greater engagement in smoking, drinking, and selfinduced vomiting than non-bored individuals [32] and more sensation-seeking behaviors in general [33].…”
Section: Dynamic Indices Of Healthmentioning
confidence: 99%
“…In earlier research, we could demonstrate that the boredom increases nostalgic memories , social identification with ingroups rather than outgroups (Van Tilburg & Igou, 2011b), and adoptions of more extreme political attitudes (Van Tilburg & Igou, 2016c), and increased pro-social behavior (Van Tilburg & Igou, 2016a). Recently, it was also found that boredom increases unhealthy eating (Koball, Meers, Storfer-Isser, Domoff, & Musher-Eizenman, 2012) as a means to reduce the salience of the meaning threat caused by boredom (Moynihan, Van Tilburg, Igou, Wisman, Donnelly, & Mulcair, 2015). The converging evidence that boredom serves as an existential threat is consistent with our current findings and such evidence validates the notion that a sense of meaning in life is a central human need, associated with psychological processes that cope with meaning threats in order to establish and re-establish meaning in life.…”
Section: Discussionmentioning
confidence: 99%
“…In recruitment, all participants self-identified as emotional eaters. Prior to the study, users filled out a pre-experiment survey that asked about their emotional eating patterns, called the Emotional Eating Scale [20]. All participants were given a demonstration of the EmoTree app, and they were given instructions on how and when to use the software.…”
Section: Study 1: Gather Emotional Eating Patternsmentioning
confidence: 99%